1981
DOI: 10.1159/000182027
|View full text |Cite
|
Sign up to set email alerts
|

Complement and Glomerular Disease – A Natural History Study

Abstract: Over a 5-year period we have performed sequential measurements of a range of complement components in 127 patients. Each had a well-characterised glomerular lesion and there was no evidence of an underlying connective tissue disorder. In 17 patients with varied histopathology, who did not have C3 nephritic factor, there was a persisting complement defect which was present during remission in the patients we were able to study. The finding of such defects is consistent with the thesis that primary complement sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1983
1983
1989
1989

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…This, in turn, could lead to or exacerbate IC-mediated diseases. Indeed, failure of the normal operation of the mechanisms described above may explain the paradox of the predisposition of patients with congenital complement deficiency to IC-mediated diseases (13,(31)(32)(33)(34)(35), the apparent greater likelihood of relapse of systemic lupus erythematosus in patients who are persistently hypocomplementemic (36)(37)(38), and the association of IC-mediated glomerulonephritis in patients who are hypocomplementemic due to the activity of C3 nephritic factor (39,40). These observations suggest that complement levels and the erythrocyte CR, receptor in primates may be important factors in the defense against IC-mediated diseases.…”
Section: Discussionmentioning
confidence: 99%
“…This, in turn, could lead to or exacerbate IC-mediated diseases. Indeed, failure of the normal operation of the mechanisms described above may explain the paradox of the predisposition of patients with congenital complement deficiency to IC-mediated diseases (13,(31)(32)(33)(34)(35), the apparent greater likelihood of relapse of systemic lupus erythematosus in patients who are persistently hypocomplementemic (36)(37)(38), and the association of IC-mediated glomerulonephritis in patients who are hypocomplementemic due to the activity of C3 nephritic factor (39,40). These observations suggest that complement levels and the erythrocyte CR, receptor in primates may be important factors in the defense against IC-mediated diseases.…”
Section: Discussionmentioning
confidence: 99%
“…These are usefully differentiated by sequential study, to which the prolonged regular follow-up for a natural history study lends itself. We have reported previously evidence de rived during this study of both varying and genetically determined defects in the complement and reticulo-en dothelial systems [13,14].…”
Section: Other Genetically Associated Immunological Factors and Glomementioning
confidence: 78%
“…case those of other reported mesangial glomerulonephropathies [9][10][11][12], Several recent publications have focused upon an association between abnormalities in the complement system and glomerulonephritis [21][22][23][24], Mallicket al [21] using discriminant analysis showed that some circulating complement component levels, assessed in relation to each other, discriminated between proliferative and membranous subgroups and had prognostic signifi cance. Russell el al.…”
Section: Discussionmentioning
confidence: 90%